A Reaction‐Induced Localization of Spin Density Enables Thermal C−H Bond Activation of Methane by Pristine FeC4+. Issue 56 (13th August 2019) - Geng, Caiyun; Li, Jilai; Weiske, Thomas; Schwarz, Helmut
Abstract: The reactivity of the cationic metal‐carbon cluster FeC4 + towards methane has been studied experimentally using Fourier‐transform ion cyclotron resonance mass spectrometry and computationally by high‐level quantum chemical calculations. At room temperature, FeC4 H + is formed as the main ionic product, and the experimental findings are substantiated by labeling experiments. According to extensive quantum chemical calculations, the C−H bond activation step proceeds through a radical‐based hydrogen‐atom transfer (HAT) mechanism. This finding is quite unexpected because the initial spin density at the terminal carbon atom of FeC4 +, which serves as the hydrogen acceptor site, is low. However, in the course of forming an encounter complex, an electron from the doubly occupied sp ‐orbital of the terminal carbon atom of FeC4 + migrates to the singly occupied π*‐orbital; the latter is delocalized over the entire carbon chain. Thus, a highly localized spin density is generated in situ at the terminal carbon atom. Consequently, homolytic C−H bond activation occurs without the obligation to pay a considerable energy penalty that is usually required for HAT involving closed‐shell acceptor sites. The mechanistic insights provided by this combined experimental/computational study extend the understanding of methane activation by transition‐metal carbides and add a new facet to the dizzying mechanistic landscape of hydrogen‐atom transfer. Abstract : Getting together : Radical‐type hydrogen‐atom transfer transpires by localized spin density generated in situ once the reaction partners approach each other.